Mathematics Course-Taking in Rural High Schools - Rick Anderson; Beng Chang (Journal of Research in Rural Education, 2011)
Using data from the 2005 NAEP High School Transcript Study, this paper examines the mathematics course-taking of rural high school students. Although several studies indicate rural high school students' mathematics achievement is comparable to that of students in non-rural high schools, the mathematics course-taking patterns of rural and non-rural high school graduates are not the same. The data suggest that, regardless of location, high school graduates typically earn more mathematics credits than that required for a standard diploma; however, graduates of rural high schools generally earn fewer mathematics credits than graduates from other locations. The data also suggest that, when compared to students from other locations, rural high school students tend to begin high school at a slightly lower level of mathematics and end their mathematics studies sooner, thus achieving an overall lower course-level of mathematics. Graduates from rural high schools also appear to have had substantially less access to AP mathematics courses.